Examination Of Isteshab Principle Opposition With Threesome Principles (Acquittal, Caution And Authority) By Lean On Sufficiency Possessor Idea - Javad Aliabad (Ar-Raniry: International Journal of Islamic Studies, 2015)
Bearing in mind that Isteshab principle is ranked as established principles and in proportion to other threesome principles, it locates at the top; therefore obviously in lieu of other operation principles, it acts like an indication and it has priority in opposition with acquittal principle, caution and authority with all kinds and fundamentalists have consensus in this case, but whatever in this problem makes difference and contention is the primacy quality of Isteshab principle which is perceptible in principle sources of some theories. Some fundamentalists considered primacy from respect of entrance; some from respect of government and some by separation of intellectual and quoted principles believing in government and entrance and some of them believing in to allocation. Therefore our try in this article is the examination of the primacy quality of Isteshab principle from fundamentalists’ viewpoint and adaption with sufficiency processor idea and sharehin. The result of essay is that apparently primacy aspect of Isteshab in proportion to other practical principles whether intellectual or religiously correct is simply from respect of entrance; because by Isteshab principle, threesome principles subject deliberately is no longer contemplated.